Hypertriglyceridemic rats fed high fat diet as a model of metabolic syndrome - Kaprinay, B; Lipták, B; Slovák, L; Švík, K; Knezl, V; Sotníková, R; Gáspárová, Z (Physiological research, 2016)
People with metabolic syndrome have higher risk of cardiovascular diseases then those without. The aim of the work was to investigate whether high fat diet administered to Prague hereditary hypertriglyceridemic (HTG) rats can induce signs of metabolic syndrome (MetS). Our results showed that HTG rats fed high fat diet (HTGch) had disturbed glucose metabolism and also lipid metabolism - increased serum triacylglycerols (TAG), total cholesterol (Ch), low-density lipoprotein-Ch (LDL-Ch), and decreased high-density lipoprotein-Ch (HDL-Ch). Their livers proved markers of developing steatosis. Moreover, HTGch had increased blood pressure, yet the vascular endothelium was not significantly damaged. All these changes were accompanied with oxidative stress and tissue damage identified as increased liver concentrations of thiobarbituric acid reactive substances (TBARS) and activity of the lysosomal enzyme N-acetyl-D-glucosaminidase (NAGA). We assume that the model used may be suitable for the study of MetS with no evidence of obesity. Prolongation of the high fat diet duration might have a major impact on all parameters tested, especially on vascular endothelial function.
Keywords: Cholesterol, LDL; Hypertriglyceridemia; Rats; Metabolic Syndrome; Disease Models, Animal; Rats, Wistar; mužské pohlaví; Diet, High-Fat; krysa rodu Rattus; dieta s vysokým obsahem tuků; modely nemocí na zvířatech; zvířata; metabolický syndrom; hypertriglyceridemie; HDL-cholesterol; LDL-cholesterol; potkani Wistar; Cholesterol, HDL; Male; Animals